Membangun Kesadaran Masyarakat Pada Masa Pandemi Covid-19 - Maria Widyastuti; Laili Nur Indah Sari; Stefanny Irene Putri Maryono (IAI Darussalam, 2021)
The Purpose of implementing community service is to build public awareness during covid-19 pandemic so that they care about conditions around their homes. The method and local officials in order to obtain an overview of the existing problems. The results of community service activities are: the pandemic period causes people to rely heavily on activities at home.Children have to study at home online which causes parents to work extra to support their children. To raise awareness, a program of installing banners in strategic place, distributing masks and hand sanitizers and repairing patrol posts was carried out. With the aim of continuously reminding people to care about themselves and those around them by compling with government recommendations in dealing with the corona virus pandemic